Investigating organization of molecules that facilitates intermolecular acyl transfer in crystals: reactivity and x-ray structures of O-benzoyl-myo-inositol 1,3,5-orthoesters - Murali, Chebrolu; Shashidhar, Mysore S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (European Journal of Organic Chemsitry, 2007)
{Crystal structure analysis of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthobenzoate reveals helical organization of the molecules, remarkably similar to that observed earlier in crystals of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthoformate. Both these dibenzoates are isostructural despite the bulkier phenyl substituent in place of hydrogen. The latter compound shows highly facile intermolecular benzoyl transfer reactivity in its crystals and as anticipated from the crystal structure, the orthobenzoate indeed exhibits facile benzoyl transfer reactivity in its crystals. 2-O-Benzoyl-myo-inositol 1,3,5-orthoformate and the corresponding orthobenzoate also undergo transesterification in their crystals, but the specificity of acyl transfer is very low, and the reaction yields a mixture of products. The parameters of helical molecular assembly that facilitates acyl transfer in crystals have been investigated. A comparison of the molecular assemblies and lattice interactions in crystals of all the four compounds with the observed reactivity patterns show that facile acyl transfer reaction is brought about by a modular ``reaction tunnel''
Keywords: AOT; CdS-Ag2S; core-shell; Nanoparticles; w/o microemulsion; XPS

Efficient lipase purification using reverse micellar extraction - Gaikaiwari, Raghavendra P.; Wagh, Shilpa A.; Kulkarni, Bhaskar D. (Bioresource Technology, 2012)
Reverse micellar extraction (RME) of enzyme provides an attractive option for conventional method with the potential to achieve purification and concentration in a single step with high yield. This study presents a methodology for optimization of RME with Pseudomonas lipase as model system. Fold-purification, percent recovery and extraction time were the objective functions while the type and concentration of surfactant, contact time, pH, ionic strength, and the ratio of organic to aqueous phase were the decision variables. Under optimized conditions, the AOT (Aerosol OT (bis 2-ethylhexyl) sodium sulfosuccinate)-isooctane system gave a 15-fold purification, 80% recovery and 2.5-fold concentration of the Pseudomonas lipase with process time of 45 min. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: (Hexadicetyltrimethylammoniumbromide); AOT; CTAB; Lipase; RME